2018
DOI: 10.1097/bot.0000000000001005
|View full text |Cite
|
Sign up to set email alerts
|

Hexapod Stacked Transport for Tibial Infected Nonunions With Bone Loss: Long-Term Functional Outcomes

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Despite advancements in surgical techniques, nonunion remains a serious therapeutic issue [2-7, 9, 10, 12-19], as it often requires comprehensive surgical treatment involving resection of damaged bone and soft tissues, excision of the focus of infection, and secondary elongation and realignment of the affected bone segment following bone transport [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][17][18][19]. While evaluating treatment outcomes in nonunion of the tibia, the majority of authors focus on whether or not bone union was achieved [30][31][32][33]. However, bone union may be only short term, as some patients develop re-fracture [1,19], which necessitate further treatment and adversely affect long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advancements in surgical techniques, nonunion remains a serious therapeutic issue [2-7, 9, 10, 12-19], as it often requires comprehensive surgical treatment involving resection of damaged bone and soft tissues, excision of the focus of infection, and secondary elongation and realignment of the affected bone segment following bone transport [1][2][3][4][5][6][7][9][10][11][12][13][14][15][16][17][18][19]. While evaluating treatment outcomes in nonunion of the tibia, the majority of authors focus on whether or not bone union was achieved [30][31][32][33]. However, bone union may be only short term, as some patients develop re-fracture [1,19], which necessitate further treatment and adversely affect long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies mentioned above [30][31][32][33] assessed the proportion of patients with maintained bone union. In our study, maintained bone union was observed in 95.1% of patients at the follow-up visit at least 2 years after treatment, which indicates excellent long-term treatment outcomes in nonunion of the tibia treated with the Ilizarov method.…”
Section: Discussionmentioning
confidence: 99%
“…A number of techniques have been described to manage deficiencies, including the induced membrane technique, 1 vascularized fibula grafting, 2 acute shortening then lengthening, 3 and bone transport utilizing monolateral, 4 , 5 Ilizarov, 6 , 7 or hexapod fixators. 8 …”
Section: Introductionmentioning
confidence: 99%
“…External fixation-based treatment is used extensively for shortening, managing bone loss, and treating limb deformity. 14 16 Some studies have investigated the degree of satisfaction of EF treatment, but no previous work has explored patient-reported satisfaction or investigated the nature of the specific problems 17 associated with such treatment and whether patients would have EF treatment again. Complaints related to EF mostly stemmed from the “pain” and “size of EF”; the same was true for those who were satisfied and those dissatisfied patients who did not want EF treatment again.…”
Section: Discussionmentioning
confidence: 99%